2016
DOI: 10.2341/15-120-lit
|View full text |Cite
|
Sign up to set email alerts
|

Restoration Survival: Revisiting Patients' Risk Factors Through a Systematic Literature Review

Abstract: A literature review was conducted to investigate the influence of patient-related factors on restoration survival in posterior permanent teeth as well as to report the methods used to collect these factors. The selection of articles on longitudinal clinical studies investigating the survival of posterior restorations (except full crowns and temporary fillings) and including patient-related factors was performed by applying predefined criteria. The review was organized into two parts, the first describing how p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 91 publications
(212 reference statements)
1
39
0
6
Order By: Relevance
“…Since the current restorative composites seem not to be the problem anymore 5 , more recent literature indicates that other factors have a predominant effect on the clinical performance of composite restorations. 12 These may include factors related to the patient (age, caries and occlusal stress risk, socioeconomic status) and the professional (age, gender, clinical experience). Establishing risk factors and indicating their main reasons might facilitate dentists' restorative treatment decisions, and consequently increase restorative longevity and reduce costs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the current restorative composites seem not to be the problem anymore 5 , more recent literature indicates that other factors have a predominant effect on the clinical performance of composite restorations. 12 These may include factors related to the patient (age, caries and occlusal stress risk, socioeconomic status) and the professional (age, gender, clinical experience). Establishing risk factors and indicating their main reasons might facilitate dentists' restorative treatment decisions, and consequently increase restorative longevity and reduce costs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Currently, several therapeutic approaches have been applied to reduce the frequency and/or intensity of SB. [1][2][3] Currently, several therapeutic approaches have been applied to reduce the frequency and/or intensity of SB.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have already shown that "older" children Metz et al, 2015], with severe decay [Bücher et al, 2014], from low income [Demarco et al, 2012;Correa et al, 2013;van de Sande et al, 2013van de Sande et al, , 2016Metz et al, 2015] had significantly lower survival probabilities in their restorations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was recommended that the assessment of patient factors, such as socioeconomic status, caries risk/ activity/severity, and oral hygiene (among others), should become part of clinical studies investigating restoration survival, since several of these factors were shown to influence the failure of restorations [van de Sande et al, 2016]. A recent retrospective study comparing "complete" and "selective" caries removal in young permanent molars demonstrated that, regardless of caries removal technique, the restorations showed a restricted survival in patients with high caries activity and gingivitis [Casagrande et al, 2016].…”
mentioning
confidence: 99%